Analisis Komparatif Tingkat Kesehatan Bank dengan Metode RGEC dan Zmijewski pada Bank Swasta dan Bank BUMN - Paramita Nidan Paramesti; Mulyanto Nugroho (Jurnal Kendali Akuntansi, 2024)
This study aims to see how the difference in financial performance between state-owned banks and national private banks through analysis from 2019 to 2022, using the RGEC approach to measure the level of bank health and the Zmijewski model to measure financial distress. With descriptive and comparative research types, as well as a quantitative approach, secondary data from four state-owned banks (Mandiri, BRI, BNI, BTN) and four private banks (BCA, CIMB, Danamon, Permata) were used. The analysis shows that private banks and state-owned banks do not have significantly different health levels in terms of risk profile (LDR and NPL), GCG, and earnings (NIM, ROA, BOPO). However, there are differences in the capital aspect (CAR). Overall, based on the Zmijewski X-score method, between private banks and state-owned banks do not have significantly different financial distress conditions. In conclusion, from 2019 to 2022, both state-owned banks and private banks show healthy financial conditions. Even though there are differences in the capital aspect, the overall health of state-owned banks is not significantly different from private banks.